The Effectiveness of Group Counseling with Self Talk and Sociodrama Techniques to Reduce Communication Apprehension - Haryanto, Haryanto; Sugiharto, Sugiharto; Awalya, Awalya (Jurnal Bimbingan Konseling, 2023)
Communication apprehension is potentially able to lead social and interpersonal barriers. Hence, this research aimed to verify the effectiveness of group counseling with self-talk and sociodrama techniques to reduce the communication apprehension of students at MAN 2 Banyumas. In conducting this research, the researchers used an experimental method with a randomized controlled trials design. From 21 research subjects selected from 355 students of MAN 2 Banyumas, 2 students had high communication apprehension. By using an objective sampling technique, 7 students were divided into 3 experimental groups. Findings revealed that the group counseling with self-talk and sociodrama techniques was positively effective to reduce communication apprehension. It can be seen from the increase in the experimental group scores before and after the tests. Further, the self-talk was more effective than socio drama in reducing students’ communication apprehension. Entrenched from the findings, it is suggested to use group counseling with self-talk and sociodrama techniques an effort to reduce students’ communication apprehension.